Severe Hypercalcemia Complicating Recovery of Acute Kidney Injury due to Rhabdomyolysis - Hechanova, Lisa Aimee (International Scientific Literature, Inc., 2014)
Patient: Male, 23 Final Diagnosis: Rabdomyolysis Symptoms: Cardiac arrest • cardiac arrhythmia • hypercalcemia Medication: — Clinical Procedure: — Specialty: — OBJECTIVE: Unusual clinical course BACKGROUND: Rhabdomyolysis is frequently complicated by multiple electrolyte abnormalities, including hyperkalemia, hyperphosphatemia, and hypo/hypercalcemia. Hypercalcemia can be severe and life-threatening. CASE REPORT: A 23-year-old white male suffered severe trauma to his lower extremities after a motor vehicle accident, leading to severe muscle damage, cardiac arrhythmia, cardiac arrest, and oliguric acute kidney injury (AKI), requiring hemodialysis treatment. As expected, he was hypocalcemic during the oliguric phase but during the diuretic phase he developed severe symptomatic hypercalcemia requiring hemodialysis treatment in spite of volume replacement and administration of pamidronate. Hypercalcemia reached a peak of 17.1 mg/dL, corrected for serum albumin and urine output was as high as 11.9 liters daily. Hypercalcemia lasted for 3 weeks and then it returned back to normal levels. Plasma levels of 25-OH and 1–25(OH)2 vitamin D were low, intact parathyroid hormone level was appropriately suppressed, and 24-hour urine calcium was 1194 mg (normal up to 350 mg/daily). Mobilization of calcium from calcium phosphate deposits in the injured muscles seems to be the main reason for hypercalcemia and hypercalciuria in rhabdomyolysis-induced AKI. CONCLUSIONS: Hypercalcemia is not uncommon during the recovery phase of ATN. Unattended, it can cause severe morbidity and even mortality. Fluid administration, pamidronate, and calcium-free dialysis are some methods used to correct severe hypercalcemia. Over time, hypercalcemia improves in almost all cases.